Shifts in habitat suitability and the conservation status of the Endangered Andean cat Leopardus jacobita under climate change scenarios - Bennett, M; Marquet, P; Sillero-Zubiri, C; Marino, J (Cambridge University Press, 2017)
Organisms adapted to life at high elevations are particularly threatened by climate change, which can cause them to become isolated on mountain tops, yet their responses may vary according to their position in the food chain and their ecological flexibility. Predicting the future distributions of such organisms requires fine-tuned species-specific models. Building on a previous ecological niche model, we explored shifts in the suitability of habitats for the Endangered Andean cat Leopardus jacobita, and assessed how these will be represented within existing protected areas in the future. Using a robust set of presence records and corrected climate surfaces, we applied the Maxent algorithm to model habitat suitability for this carnivore and for its preferred prey, the mountain viscacha Lagidium viscacia. Our predictions indicate that the areas climatically suitable for Andean cats could contract by up to 30% by 2080 under the most pessimistic scenario, with an overall upwards shift of 225 m and a polewards displacement of 98–180 km. The predicted range contraction was more pronounced in the species’ core range, in the Bolivian and Peruvian Andes, whereas suitable conditions may increase in the southern range in Patagonia. Bolivia and Peru are predicted to suffer the most marked decline in habitat representativeness within protected areas. The southern range appears to be less vulnerable to climate change, offering opportunities for the conservation of this genetically distinct population. We discuss the value and limitations of using species distribution modelling to assess changes in the potential distribution and conservation status of this and other Andean species.